Modelling of neutrophil dynamics in children receiving busulfan or treosulfan for haematopoietic stem cell transplant conditioning. Issue 8 (3rd March 2020) - Solans, Belén P.; Chiesa, Robert; Doncheva, Bilyana; Prunty, Helen; Veys, Paul; Trocóniz, Iñaki F.; Standing, Joseph F.
Abstract : Aims: Busulfan and treosulfan are cytotoxic agents used in the conditioning regime prior to paediatric haematopoietic stem cell transplantation (HSCT). These agents cause suppression of myeloid cells leaving patients severely immunocompromised in the early post‐HSCT period. The main objectives were: (i) to establish a mechanistic pharmacokinetic–pharmacodynamic (PKPD) model for the treatment and engraftment effects on neutrophil counts comparing busulfan and treosulfan‐based conditioning, and (ii) to explore current dosing schedules with respect to time to HSCT. Methods: Data on 126 patients, 72 receiving busulfan (7 months–18 years, 5.1–47.0 kg) and 54 treosulfan (4 months–17 years, 3.8–35.8 kg), were collected. In total, 8935 neutrophil count observations were recorded during the study period in addition to drug concentrations to develop a mechanistic PKPD model. Absolute neutrophil count profiles were modelled semimechanistically, accounting for transplant effects and differing set points pre‐ and post‐transplant. Results: PK were best described by 2‐compartment models for both drugs. The Friberg semimechanistic neutropenia model was applied with a linear model for busulfan and a maximum efficacy model for treosulfan describing drug effects at various stages of neutrophil maturation. System parameters were consistent across both drugs. The HSCT was represented by an amount of progenitor cells enhancing the neutrophils' proliferation and maturation compartments. Alemtuzumab was found to enhance the proliferative rate under which the absolute neutrophil count begin to grow after HSCT. Conclusion: A semimechanistic PKPD model linking exposure to either busulfan or treosulfan to the neutrophil reconstitution dynamics was successfully built. Alemtuzumab coadministration enhanced the neutrophil proliferative rate after HSCT. Treosulfan administration was suggested to be delayed with respect to time to HSCT, leaving less time between the end of the administration and stem cell infusion.